Mekanisme Good Corporate Governance dan Kualitas Aset Perbankan di Masa Pandemi Covid-19 - Damayanti, I Gusti Ayu Agung; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 32 No 11 (2022)DO - 10.24843/EJA.2022.v32.i11.p01, 2022)
The aim of this research is to analyze the effect of the Good Corporate Governance mechanism on the quality of banking industry assets during the Covid-19 pandemic. This research was conducted at banking companies listed on the Indonesia Stock Exchange in 2020. The data analysis technique uses multiple linear regression analysis. The results of the analysis show that the board of independent commissioners has a negative effect on non-performing loans, thus indicating that the quality of banking assets is getting better. Board of directors with accounting and finance education background, audit committee with accounting and finance education background, as well as managerial and institutional ownership have no effect on the quality of banking assets. The proportion of an independent board of commissioners determines the quality of banking assets during the Covid-19 pandemic. Keywords: Asset Quality; Non-Performing Loan; Good Corporate Governance Mechanism